ANALISIS EFEKTIVITAS PROSES REKRUTMEN SEBELUM DAN SESUDAH MENGGUNAKAN SIEMEN PADA RSUD SITI FATIMAH AZ-ZAHRA - Ulandari, Winda; Trisninawati (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this study was to determine the comparison before and after using SIEMEN in the recruitment process at Siti Fatimah Az-zahra Hospital. In this study using three informants. The method used in this research is comparative descriptive with a qualitative approach. The analysis used is data reduction, data presentation, and conclusions. Based on the study conducted, it can be concluded that the recruitment process using SIEMEN is more effective than recruitment before using SIEMEN or offline recruitment. This can be seen from the answers that have been submitted by informants that the recruitment process using SIEMEN has many advantages and advantages, including cost savings, ease of recruitment, ease of use for organizations, improving the employee recruitment process, and success in finding employees as needed. The effectiveness of recruitment using SIEMEN from the target aspect at Siti Fatimah Az-zahra Hospital is very effective but there are still obstacles in the recruitment process such as many applicants who have difficulty verifying the applicant's own email. When viewed in terms of cost, energy, and time spent on the recruitment process using SIEMEN is not classified as much when compared to recruitment before using SIEMEN.